Surface Treatments with Dichloromethane to Eliminate Printing Lines on Polycarbonate Components Printed by Fused Deposition Modelling Technology - Suárez Macías, Jorge; Terrones Saeta, Juan María; Iglesias, Francisco Javier; Corpas Iglesias, Francisco Antonio (MDPI, 2020)
Additive manufacturing, framed within the Industry 4.0. concept, is one of the processes that has witnessed greater development in the last years. Within this subject fused deposition modelling (FDM) printing technology is mainly dedicated to polymers and capable of providing components or elements of sufficient quality for different sectors. However, due to the process there can be a series of surface irregularities, which although they do not affect the required dimensional tolerances, they can cause problems in the useful life of the printed object in its interactions with the environment, as well as poor aesthetic qualities. Based on the above, this paper presents a series of chemical surface treatments capable of providing a surface that avoids undesired printing lines. For this purpose, fast, economical and environmentally sustainable treatments are used that obviously do not deteriorate the structure of the component or degrade the material surface. A complete study is therefore presented in which the different variables of the process are evaluated, as well as those of the printing technology, such as the layer height, coating, infill density, etc. The development of this project achieves a field of application of the detailed chemical treatment to obtain smooth surfaces, without degradation of the final part and with the appropriate dimensional tolerances.
Keywords: 3D printing; additive manufacturing; fused deposition modeling; polycarbonate; surface treatments